018 One Step Beyond: Working in partnership with CCGs to extend access to Bereavement Services. (1st October 2013) - Patel, June; Helm, Sarah Popplestone; Westwood, Debbie
Abstract : Aims: The service aims to - Provide access to bereavement support for all bereaved people irrespective of age, culture disability and gender - Assess bereavement need and signpost people pre and post bereavement to bereavement services within their locality - Extend access to advice 24/7 supported by the development of a bespoke bereavement website www.bereavementsupportworcestershire.org.uk telephone help-line service, Counselling and Social Work support - Raise professional awareness about grief by providing bespoke education and training - Raise awareness of the bereavement process and coping strategies of bereaved individuals and families by education and group support. Approach A formal tendering process resulted in securing a three year NHS contract. A multi-agency project group was formed, including a service user, to develop the operational service model in accordance with the NHS service specification. Outcomes - Widening access of bereavement support to adults and children experiencing sudden death from suicide, RTAs' and unexpected deaths - Multi-agency engagement in shaping operational model - Rapid access to social work and counselling social for the bereaved following self-referral and referrals from Primary Care - Positive evaluations from services users and GPs' - Service user involvement in the formal media launch with South Worcestershire CCG - 193 professionals have attended education programme and positively evaluated - 7401 hits to access information on bereavement website.